Enhancing transparency of climate change mitigation under the Paris Agreement Lessons from experience - Briner, Gregory (OECD/IEA Climate Change Expert Group Papers, 2017)
An enhanced transparency framework will be a central component of the post-2020 international climate policy regime under the Paris Agreement, underpinning the dynamic process of updating nationally determined contributions (NDCs) and providing input to the global stocktakes of progress towards the long-term goals of the Paris Agreement. The enhanced transparency framework will apply to all Parties, with flexibility in light of capacities. This paper highlights lessons learned from the existing transparency framework for mitigation that can help inform the development of modalities, procedures and guidelines for the enhanced transparency framework under the Paris Agreement. It outlines how clearer and more detailed reporting guidelines could be developed for communication of the mitigation components of NDCs and reporting on progress in their implementation and achievement, based on NDC type